Field notes contributed by Ann Johnson, fall 1993 - Johnson, Annet al (1993)
Fall report of birds and locations contributed by Ann Johnson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed